新加坡华语社区剧场 ：以实践剧场为例 = Chinese community theatre in Singapore : a case study of the theatre practice - 陈美燕 Tan, Serene Mei Yan (2011)
社区剧场是个多元化的概念，在不同的社会里持有不同意义。实践剧场是第一个将剧场带进社区的本地剧团，从1986年创建至今，它将各种不同类型的剧场带给社区的民众。实践剧场的社区剧场大致上可以分为三个阶段，而每个阶段所呈现的社区剧场的性质以及其意义都有所不同。虽然身为双语剧团，实践剧场不但没忽略华语剧场，反而更努力发展本地华语社区剧场。本论文将探讨实践剧场从创建至今在华语社区剧场的参与，以及随着观众、社会和剧团本身的改变，其社区剧场如何随之变化，并从中探析这些参与和改变对社会的意义。Community theatre is a diversified concept and it holds different meanings in different societies. As the first local theatre group to bring theatre to the community, The Theatre Practice (TTP) has brought many types of theatre to the people since it was set up in 1986. Community theatre by TTP can be generally categorized into three periods, whereby the nature and the meaning of each period's community theatre vary. As a bilingual theatre group, TTP not only did not neglect the Chinese theatre, in fact, it went to greater lengths to develop Chinese theatre in Singapore. This thesis would be discussing TTP's involvement in Chinese community theatre since its establishment, and how community theatre has changed over the years with the changes of the audience, society and TTP itself. From then, the significance of TTP's involvement in Chinese community theatre would be discussed.